Are there monitoring benefits to institutional ownership? Evidence from seasoned equity offerings - Demiralp, Ilhan; D'Mello, Ranjan; Schlingemann, Frederik P.; Subramaniam, Venkat (Journal of Corporate Finance, 2011)
We provide new evidence on the monitoring benefits from institutional ownership by analyzing the impact of institutional ownership on stock price and operating performance following seasoned equity offerings, a setting where the effects of monitoring are likely to be especially important. We find that announcement returns are positively and significantly related to total and active institutional ownership levels and concentration. Post-issue stock returns are positively and significantly related to the contemporaneous post-issue changes in total and active institutional ownership and the concentration of their shareholdings. Operating performance improvements are also related to institutional monitoring in the one, two, and three years following the equity issue. Our results continue to hold even after accounting for the possibility that institutional investors have an informational advantage that enables them to identify and invest in subsequently better performing firms. We also empirically eliminate the possibility that our findings are driven by institutions buying past winners and selling past losers as a way to window-dress their portfolio holdings.